2014
DOI: 10.1016/j.ijgo.2014.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of a women‐only, sex‐work‐specific drop‐in center and links with sexual and reproductive health care for sex workers

Abstract: Objective To longitudinally examine female sex workers’ (FSWs’) uptake of a women-only, sex-work-specific drop-in service and its impact on their access to sexual and reproductive health (SRH) services. Methods For the present longitudinal analysis, data were drawn from the AESHA (An Evaluation of Sex Workers’ Health Access) study, a community-based, open, prospective cohort of FSWs from Vancouver, BC, Canada. Data obtained between January 2010 and February 2013 were analyzed. Participants are followed up on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 22 publications
(33 reference statements)
1
44
0
Order By: Relevance
“…The effective contribution of DICs to provide SRH services to vulnerable populations such as FSWs has been noted in other studies in Laos and Canada [40,42]. Another study in Mysore, India documented an increase in care seeking from DICs from 56% at baseline to 89.6% at follow up (more than two years after baseline) and was significantly associated with improvements in condom use and reducing STIs [43].…”
Section: Discussionmentioning
confidence: 62%
“…The effective contribution of DICs to provide SRH services to vulnerable populations such as FSWs has been noted in other studies in Laos and Canada [40,42]. Another study in Mysore, India documented an increase in care seeking from DICs from 56% at baseline to 89.6% at follow up (more than two years after baseline) and was significantly associated with improvements in condom use and reducing STIs [43].…”
Section: Discussionmentioning
confidence: 62%
“…The occasional women-/youth-/sexual minority-centered programming may have exclusive hours (e.g., women-only hours; youth-only hours) or locations for members where people feel safer, free from harassment, and the fear of encountering abuse from former partners or people with discriminatory beliefs. Research in this population supports the effectiveness of women-only spaces [48]. Many services are general and open to everyone, but this approach can paradoxically exclude individuals who are more vulnerable to food insecurity because safety from abuse and discrimination in a public environment is not guaranteed [38].…”
Section: Discussionmentioning
confidence: 99%
“…Jeal & Salisbury, 2007; Scorgie et al, 2013; Socías et al, 2015). Canadian researchers have also suggested that SWs have inadequate access to sexual and reproductive health services and cervical screening (Kim et al, 2015). As many of these unmet health needs are persistent in settings where high-quality health care is available and contact with general practitioners is frequently reported in the general population (Nikki Jeal & Salisbury, 2004; N.…”
mentioning
confidence: 99%